High Thermoelectric Performance of In4Se3‑Based Materials and the Influencing Factors - Yin, Xin; Liu, Jing-Yuan; Chen, Ling; Wu, Li-Ming (Accounts of chemical research, 2018)
Conspectus Materials that can directly convert electricity into heat, i.e., thermoelectric materials, have attracted renewed attention globally for sustainable energy applications. As one of the state-of-the-art thermoelectric materials, In4Se3 features an interesting crystal structure of quasi-two-dimensional sheets comprising In/Se chains that provide a platform to achieve a Peierls distortion and support a charge density wave instability. Single-crystal In4Se3−δ (δ = 0.65) shows strong anisotropy in its thermoelectric properties with a very high ZT of 1.48 at 705 K in the b–c plane (one of the highest values for an n-type thermoelectric material to date) but a much lower ZT of approximately 0.5 in the a–b plane. Because of the random dispersion of grains and the grain boundary effect, the electrical transport properties of polycrystalline In4Se3 are poor, which is the main impediment to improve their performance. The In4-site in the In4Se3 unit cell is substitutional for dopants such as Pb, which increases the carrier concentration by 2 orders of magnitude and the electrical conductivity to 143 S/cm. Furthermore, the electrical conductivity markedly increases to approximately 160 S/cm when Cu is doped into the interstitial site but remains as low as 30 S/cm with In1/In2/In3-site dopants, e.g., Ni, Zn, Ga, and Sn. In particular, the In4-site dopant ytterbium introduces a pinning level that highly localizes the charge carriers; thus, the electrical conductivity is maintained within an order of magnitude of 30 S/cm. Meanwhile, ytterbium also creates resonance states around the Fermi level that increase the Seebeck coefficient to −350 μV/K, the highest value at the ZT peak. However, the maximum solubility of the dopant may be limited by the Se-vacancy concentration. In addition, a Se vacancy also destroys the regular lattice vibrations and weakens phonon transport. Finally, nanoinclusions can effectively scatter the middle wavelength phonons, resulting in a decrease in the lattice thermal conductivity. Because of the multiple-dopant strategy, polycrystalline materials are competitive with single crystals regarding ZT values; for instance, Pb/Sn-co-doped In4Pb0.01Sn0.04Se3 has ZT = 1.4 at 733 K, whereas In4Se2.95(CuI)0.01 has ZT = 1.34 at 723 K. These properties illustrate the promise of polycrystalline In4Se3-based materials for various applications. Finally, the ZT values of all single crystalline and polycrystalline In4Se3 materials have been summarized as a function of the doping strategy applied at the different lattice sites. Additionally, the correlations between the electrical conductivity and the Seebeck coefficient of all the polycrystalline materials are presented. These insights may provide new ideas in the search for and selection of new thermoelectric compounds in the In/Se and related In/Te, Sn/Se, and Sn/Te systems.